Exercise-induced mitochondrial protection in skeletal muscle of ovariectomized mice: A myogenic E2 synthesis-independent mechanism - Xu Tian; Yi Hu; Tao Li; Fangfang Yu; Tingting Li; Xiangyang Tian; Yiwei Feng; Qiuling Zhong; Yifan Meng; Wei Chen; Rengfei Shi (Redox Biology)
Background: Skeletal muscle, a 17β-estradiol (E2)-sensitive tissue, is prone to accelerated aging due to postmenopausal E2 deficiency and subsequent mitochondrial dysfunction. While exogenous E2 treatment has been shown to protect against mitochondrial damage in ovariectomized rodents, the impact of exercise-induced local E2 production in skeletal muscle on mitochondrial function remains to be determined. This study investigated exercise-mediated mitochondrial protection in ovariectomized mice and the contribution of myogenic E2. Methods: Female C57BL/6J mice (8-week-old) were divided into Sham, OVX, and OVX + ET groups (N = 12). OVX mice underwent bilateral ovariectomy, with the OVX + ET group performing 8 weeks of treadmill exercise starting 10 weeks post-surgery. Functional tests (grip strength, fatigue resistance) and gastrocnemius analyses (morphology, mitochondrial function, E2/antioxidant levels, and protein expression) were conducted. Parallel experiments in muscle-specific aromatase knockout (MS-ARO-CKO) mice included E2 supplementation via subdermal pellets. Results: 18 weeks after ovariectomy (OVX), C57BL/6J mice exhibited significant reductions in grip strength (∼30 %), rotarod performance (∼57 %), and grid hanging performance (∼92 %). Concomitantly, OVX led to marked decreases in mitochondrial respiration (p < 0.05) and antioxidant capacity (p < 0.05) in the gastrocnemius muscle, accompanied by alterations in mitochondrial quality control and antioxidant signaling proteins (p < 0.05). Exercise intervention effectively attenuated these OVX-induced deficits, accompanied by a 66 % increase in E2 levels and upregulation of aromatase (ARO) activity and expression (p < 0.05). In MS-ARO-CKO mice model, exercise failed to improve the impaired antioxidant capacity induced by OVX. However, exercise, similar to estrogen supplementation, restored mitochondrial function and related protein expression abnormalities induced by OVX (p < 0.05). Conclusions: Our findings demonstrate that the protective effects of exercise on skeletal muscle mitochondria involve multiple mechanisms, independent myogenic E2 Synthesis, providing novel insights for improving skeletal muscle health in postmenopausal women.